Directorate of Education, Delhi - Sharma, Rajeev; Dixit, Mukund; Verma, Sanjay (London : SAGE Publications Ltd, 2017)
The market share of Chartered Cabs is affected by new entrants in Ahmedabad. In addition, their operational costs are soaring due to excessive dry run costs. Due to immense competition, Chartered needs to focus on high service quality delivery and also minimize its operational costs. This case will allow the participants to understand the operational complexities of a cab service provider and also arrive at alternate strategies to minimize costs.
Originally published inSharma, R., Dixit, M., & Verma, S. (2012). Directorate of Education, Delhi. RJMC0019. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Chartered Cabs; Taxicabs -- Cost of operations -- India -- Delhi Metropolitan Area; Taxicab drivers -- India -- Delhi Metropolitan Area; Taxicab industry -- India -- Delhi Metropolitan Area